2016
DOI: 10.3389/fpsyg.2015.02062
|View full text |Cite
|
Sign up to set email alerts
|

Recognition Memory is Improved by a Structured Temporal Framework During Encoding

Abstract: In order to function optimally within our environment, we continuously extract temporal patterns from our experiences and formulate expectations that facilitate adaptive behavior. Given that our memories are embedded within spatiotemporal contexts, an intriguing possibility is that mnemonic processes are sensitive to the temporal structure of events. To test this hypothesis, in a series of behavioral experiments we manipulated the regularity of interval durations at encoding to create temporally structured and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 48 publications
6
42
7
Order By: Relevance
“…Temporal expectations can be generated in different ways, such as by informative associations between events, by varying the probability of when an event will occur, or the presence of a pattern or rhythm, and these expectations can be generated automatically or voluntarily (Nobre & van Ede, 2018). Such temporal expectation has previously been shown to provide a benefit to memory, and the behavioural findings reported here are in line with the study by Thavabalasingam et al (2016), who manipulated temporal structure by presenting stimuli in a fixed repeating sequence of presentation timings (i.e., 100 ms; 500 ms; 1000 ms; 2000 ms). In their study the presentation of items in the sequence condition was predictive, meaning that participants were able to learn to expect items to be presented at particular points in time, and they reported greater recognition for items presented in sequence relative to those with random onset timings.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Temporal expectations can be generated in different ways, such as by informative associations between events, by varying the probability of when an event will occur, or the presence of a pattern or rhythm, and these expectations can be generated automatically or voluntarily (Nobre & van Ede, 2018). Such temporal expectation has previously been shown to provide a benefit to memory, and the behavioural findings reported here are in line with the study by Thavabalasingam et al (2016), who manipulated temporal structure by presenting stimuli in a fixed repeating sequence of presentation timings (i.e., 100 ms; 500 ms; 1000 ms; 2000 ms). In their study the presentation of items in the sequence condition was predictive, meaning that participants were able to learn to expect items to be presented at particular points in time, and they reported greater recognition for items presented in sequence relative to those with random onset timings.…”
Section: Discussionsupporting
confidence: 86%
“…Only three of the 24 participants reported awareness of the different onset timings, and recognition scores were similar in aware and unaware participants. A similar finding was reported by Thavabalasingam et al (2016), in which recognition was greater following structured than unstructured presentation timings regardless of whether or not participants were aware. This may suggest an implicit mechanism underlying the beneficial effect of temporal structure on memory.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A large body of research has 26 demonstrated that exposure to environmental rhythms influences perception and action by 27 enhancing processing at specific moments of time that align with the rhythmic beat [1-3]. More 28 recently, there has been growing interest in how environmental rhythms influence higher-order 29 cognitive processes such as memory formation [4][5][6][7]. In a series of studies, Johndro and 30 colleagues found that the timing of individual events within a rhythmic temporal stream 31 influenced memory formation [8].…”
mentioning
confidence: 99%